Colossians encouragement to walk in all wisdom as holy ones in Christ - Heil, John Paul (Early Christianity and its literature ;, 2010)
This book investigates Colossians as a "captivity" letter from the primary implied author, the imprisoned Paul, to an implied audience of mainly Gentile converts currently in danger of influence by local Jews or Jewish Christians. Utilizing a text-centered, literary-rhetorical, and audience-oriented method, it demonstrates new chiastic structures for the entire letter that progressively encourage the audience to resist deceit and conduct themselves according to all the wisdom at their disposal as holy ones in Christ.